The Relationship between Withdrawal lifestyle and Social Support pattern for People with Renal Failuer - Hiba, ‏​‏​‏​​‏​‏​​‏​‏​‏​‏​‏​‏Hasaa Omar (Journal of Humanities & Social Sciences, 2019)
The aim of the study is to know the relationship between the withdrawal lifestyle and the patterns of social support for the people who suffer from the Kidney failure and who are registrants in the King Salman Center for Kidney Diseases and King Abdullah Dialysis Charity in Riyadh .The researcher depends on the method of social survey on simple random sample style which have used on the standard of the withdrawal life style and social support which have been applied on the random sample consists of 143 persons who suffer from kidney failure and the results show that there is no associative relationship between the withdrawal life style and the social support for the people of kidney failure.Also, it resulted that the members of the study sample have manifestations of withdrawal characterizes as low in general, they also get social support on average "sometimes " from the inside and outside of the family frame generally. The results clarify that there is no statistic relationship between withdrawal life style and the social support and between the mutable age group and the date of injury of kidney failure , and there is a statistic relationship between the withdrawal life style and the social status favor for " Married , divorced and widowers " in the relationship between the social status and the withdrawal life style and favor for the "widowers and singles" in relationship between the social status and support . As well there is no statistic relationship between the social support. In the light of the results, a rand of recommendations and proposals were made to improve the life of people who suffer from kidney failure.
Keywords: withdrawal lifestyle; social support; kidney failure